Analysis of the Influence of Career Development and Work Discipline on Employee Performance which is Mediated by Organizational Culture - Muhammad Aghis Wahidu Zaman; Nasharuddin Mas (Optima Science, 2023)
This study aims to determine the effect of the influence of career development and work discipline on employee performance mediated by organizational culture. The sampling technique used in this study was purposive sampling with 105 respondents. And the data is processed through Smart Partial Least Square (PLS 4) software. The results of this study indicate that the strong influence of appropriate career development is not able to encourage increased employee performance, appropriate work discipline is able to strongly encourage increased employee performance, appropriate organizational culture is able to strongly encourage increased employee performance, appropriate career development is able to strongly encourage increased organizational culture, appropriate work discipline is able to strongly encourage increased organizational culture, organizational culture is able to be a full mediation of the effect of career development on employee performance, organizational culture is able to be a partial mediation of the effect of work discipline on employee performance.